2008
DOI: 10.1093/rpd/ncn262
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological studies of leukaemia in children and young adults around nuclear facilities: a critical review

Abstract: The existence of an increased risk of childhood leukaemia near nuclear installations is a recurrent issue. A review of the related epidemiological literature is presented here. Results for 198 nuclear sites throughout 10 countries were included in the review. In addition to local studies, 25 multi-site studies have been published for eight countries. A large variability was noticed in the quality of the data as well as in the definition of the study population and in the methods of analysis. Many studies prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 52 publications
1
48
0
3
Order By: Relevance
“…Leur revue et la revue d'autres études semblables en France (Laurier et Bard, 1999 ;Laurier et al, 2002Laurier et al, , 2008 et en Grande-Bretagne (COMARE, 2006(COMARE, , 2011 n'ont pas permis de déterminer à ce jour l'existence d'un lien de causalité entre un facteur de risque chimique ou physique et le risque observé de leucémie infantile chez les enfants de moins de 5 ans habitant dans un rayon de 5 km des centrales nucléaires tel que l'avait suggéré l'étude KiKK. Il n'en reste pas moins que le risque observé demeure inexpliqué.…”
Section: éTudes éPidémiologies Sur Les Descendants Des Travailleurs Dunclassified
See 1 more Smart Citation
“…Leur revue et la revue d'autres études semblables en France (Laurier et Bard, 1999 ;Laurier et al, 2002Laurier et al, , 2008 et en Grande-Bretagne (COMARE, 2006(COMARE, , 2011 n'ont pas permis de déterminer à ce jour l'existence d'un lien de causalité entre un facteur de risque chimique ou physique et le risque observé de leucémie infantile chez les enfants de moins de 5 ans habitant dans un rayon de 5 km des centrales nucléaires tel que l'avait suggéré l'étude KiKK. Il n'en reste pas moins que le risque observé demeure inexpliqué.…”
Section: éTudes éPidémiologies Sur Les Descendants Des Travailleurs Dunclassified
“…De plus, les revues des cas de leucémie infantile à proximité des installations nucléaires par Laurier et al (Laurier et Bard, 1999 ;Laurier et al, 2002Laurier et al, , 2008 n'ont confirmé l'existence que de trois grappes de cas de leucémie ayant persisté dans le temps, soit aux environs de Sellafield, Dounreay et Krümmel. Ces études n'ont pu mettre en évidence aucun lien de causalité entre la leucémie chez l'enfant et l'exposition environnementale à la radioactivité près des installations nucléaires ou l'exposition parentale avant la conception.…”
Section: éTudes éPidémiologies Sur Les Descendants Des Travailleurs Dunclassified
“…74 Most studies have found no associations with living close to a nuclear plant. 1,3,4,[75][76][77] Two recent case-control studies found a higher risk of leukaemia associated with residential proximity to nuclear plants. 78,79 Another study from Belarus found a strong association between thyroid cancer and fallout from the Chernobyl accident.…”
Section: 34mentioning
confidence: 99%
“…Follow-up studies have indicated that the risk decreased over time [5]. Although an explanation for the observed risk is unclear, the most likely explanation may pertain to a yet-tobe-identified infectious agent [6,7]. The German Radiological Protection Commission conducted an independent reanalysis of the KiKK study and noted several methodological limitations, and concluded that while the reasons for the observed increased risk remained unclear, multiple confounding factors could have been the cause [8].…”
Section: Introductionmentioning
confidence: 99%